The Fifth Miracle : The Search for the Origin and Meaning of Life - Davies, P. C. W (New York, NY : Simon & Schuster, 1999)
Explains our current knowledge about life's origins, focusing on recently discovered "superbugs" which may have arrived here on asteroids, and arguing that life grew from primitive information-processing systems
ch. 1. Meaning of life -- ch. 2. Against the tide -- ch. 3. Out of the slime -- ch. 4. Message in the machine -- ch. 5. Chicken-and-egg paradox -- ch. 6. Cosmic connection -- ch. 7. Superbugs -- ch. 8. Mars: red and dead? -- ch. 9. Panspermia -- ch. 10. Bio-friendly universe?
Includes bibliographical references (p. 275-291) and index
Keywords: Life -- Origin; Life